Pengaruh Content Marketing dan Electronic Word of Mouth Pada Media Sosial Instagram Terhadap Keputusan Pembelian Produk Vaseline Hand & Body Lotion - Sucia Pratiwi; Rose Rahmidani (Universitas Negeri Padang, 2023)
This study intends to certain the impact of content marketing and electronic word of mouth on Padang City residents’ decisions to purchase Vaseline hand & body lotion products. Reseacrh of this kind is casual research of this kind reaserch. The inhabitants 0f Padang City who have purchase and witnessed content marketing for Vaseline hand & body lotion good make up the study’s population. Using the Chocran formula and the purposive sampling method, the number of samples out of a total of 100 samples is determined. The information used was gathered by the distribution of questionnaires to residents of Padang City that had predetermined parameters. Using SPSS 22 as the analytical tool, descriptive and inductive analyses were performed. The findings demonstrated that content marketing and electronic word of mouth both had a substantial and positive impact on consumers’ decisions to buy products. Electronic word of mouth also had a strong and positive impact on consumers’ decisions to buy products.